PARADOKS PASAR BEBAS DAN DEMOKRASI DALAM BINGKAI KERESAHAN ETNIS - Budiyani, Annisa E. (UI Scholars Hub, 2004)
Many believe that the ongoing process of exporting free-market democracy is the best prescription for multiple ills in the so-called 'under-developed' non-western societies. The combination of free-market principles in economy and free election system of political democracy is believed to bring an ultimate solution lead to global peace, prosperity, as well as stability. These have misled us in a very critical way. Exporting free-market democracy, instead of bringing global peace, prosperity, and justice, has been the source of instability, global resentment, and, moreover, violence. Amy Chua rose up an argument that globalizing free-market democracy has been the source for worldwide group hatred and ethnic violence. It is because in most of non-western societies, live what she calls 'the market-dominant minority', ethnic minorities who, for widely varying reasons, tend under market conditions to dominante economically, often to a startling extent, the